PARADOXES IN WUTHERING HEIGHTS (1847) BY EMILY BRONTË: THE RELATIONSHIP BETWEEN HEREDITY, ENVIRONMENTS, NATURE, AND CULTURE IN THE FORMATION OF A CHARACTER’S IDENTITY - Putri, Aisyah; Nurrachman, Dian; Abd Hannan EF; Mansyur, Agus Salim; Nurul'aen, Yuyun (Universitas Islam Negeri Sunan Gunung Djati, 2025)
This research re-examines or re-analyses the paradox in the novel Wuthering Heights, but focuses on the paradox contained in the identity of the characters based on the narrator's narration. The paradox is created by the contradiction of the place where the characters live, namely nature and culture, then heredity and environment. This research discusses how these contradictions can create and become a factor in the formation of paradox in the character's identity. This research also discusses what paradoxes are found in the character's identity which is an important element in the story of Wuthering Heights. The theory used in this research is Deconstruction proposed by Jacques Derrida as the main foundation in analyzing the object. The research design used in this research is literary criticism. The approach used is an objective approach, where the focus of analysis is entirely on the object of study. The primary data source of this research is the novel Wuthering Heights (1847) by Emily Brontë and secondary data obtained from other sources such as relevant journals, books, and media articles. This research shows that the opposition of nature and culture, then heredity and environment, has no dominant side. However, these oppositions influence each other and create complexity, thus creating various paradoxes in the character's identity.